Sebaran Dan Populasi Pisang Maba (Musa Spp) Di Kabupaten Halmahera Timur - Meygyawati Abd Kadir; Rima Melati; Suryati Tjokrodiningrat; Erna Rusliana M. Saleh; Abdul Rahmat Mandea; Yusri Sapsuha (Jurnal Pertanian Khairun, 2025)
Maba bananas (Musa spp.), locally known as tele mobon, are a unique banana variety from East Halmahera Regency. They are becoming increasingly difficult to find and are at risk of local extinction due to limited cultivation efforts and scientific documentation. This study aims to identify the geographic distribution, population size, and cultivation status of Maba bananas in the region. Methods: The study was conducted over three months (July-September) in five sub-districts and 11 villages in East Halmahera Regency. A descriptive, qualitative, and quantitative approach was used, with respondents determined through snowball sampling. Data were collected through direct field observation and interviews with key informants. Results: The study showed that Maba bananas are distributed in lowland ecosystems at elevations between 7 and 97 meters above sea level. A total population of 148 individuals was identified, growing in 36 clumps. The highest population was found in Pekaulang Village (25 individuals), while the lowest population was in Titipa Village (4 individuals). Based on growth phase, the population was predominantly vegetative (145 individuals), with only three individuals in the generative phase. Most of these bananas are grown through community cultivation, but some clumps grow wild without regular maintenance.